2014
DOI: 10.1111/dme.12583
|View full text |Cite
|
Sign up to set email alerts
|

In vivo corneal confocal microscopy as a novel non‐invasive tool to investigate cardiac autonomic neuropathy in Type 1 diabetes

Abstract: This study suggests that corneal confocal microscopy could represent a new and non-invasive tool to investigate cardiac autonomic neuropathy in people with Type 1 diabetes. Larger studies are required to define the role of corneal confocal microscopy in the assessment of cardiac autonomic neuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 23 publications
(27 reference statements)
0
37
0
Order By: Relevance
“…43, 46, 48, 49, 66, 69, 70, 71, 72, 73 Diabetic peripheral neuropathy, a common complication in up to 54% of diabetic population, is a significant cause of morbidity and poor quality of life in diabetic patients. As such, early detection of high-risk patients can pre-empt the course of the disease with measures such as better foot-care to improve healthcare outcomes.…”
Section: Cornea Neuropathymentioning
confidence: 99%
See 1 more Smart Citation
“…43, 46, 48, 49, 66, 69, 70, 71, 72, 73 Diabetic peripheral neuropathy, a common complication in up to 54% of diabetic population, is a significant cause of morbidity and poor quality of life in diabetic patients. As such, early detection of high-risk patients can pre-empt the course of the disease with measures such as better foot-care to improve healthcare outcomes.…”
Section: Cornea Neuropathymentioning
confidence: 99%
“…6, 16, 17, 45, 77 Decreases in nerve fiber length in sub-basal nerve plexus have also been found to be associated with subclinical diabetic autonomic neuropathy which may be life-threatening, including cardiovascular complications such as arrhythmias or sudden cardiac deaths. 46, 71, 72 The vagal function is used as a measure of autonomic neurological function, assessed by the change of heart rate in response to breathing and posture.…”
Section: Cornea Neuropathymentioning
confidence: 99%
“…There were progressive and significant reductions in nerve-fiber density, nerve-branch density, and nerve-fiber length in patients with DAN vs healthy control and patients without DAN. Another study showed that CCM could represent a new and noninvasive tool in the diagnosis of CAN in T1DM, as corneal nerve-fiber density was lower in patients with CAN vs without CAN (based on HRV and postural hypotension) 116. This is still an evolving area of research, but could present a new noninvasive method for CAN screening and diagnosis in the future.…”
Section: Diagnosis and Screening Of Canmentioning
confidence: 99%
“…For example, an improvement in the gold standard for DPN – nerve-conduction studies – does not necessarily correlate with an improvement in CAN and vice versa, whereas if CCM, discussed earlier, were used as a measure of DPN, it may lead to a different result. Indeed, following islet-cell transplant, CCM shows improvements in corneal nerves 115,116…”
Section: Treatment Of Canmentioning
confidence: 99%
“…Among patients with type 1 diabetes, CNFD was significantly lower ( P = 0.008) in the presence of CAN, and this difference remained significant after adjustment for age, sex, type 1 diabetes duration, insulin dosage and severity of DSPN. Similarly, CNFL was significantly lower in the presence of CAN ( P = 0.005), and this difference remained significant after adjustment for type 1 diabetes duration, insulin dosage and severity of DSPN, but it lost significance after adjustment for age and sex. Tavakoli et al .…”
Section: Introductionmentioning
confidence: 97%